Legal Validity Of Power Of Attorney To Sell Which Is Preceded By A Sale And Purchase Binding Agreement On The Transfer Of Land Rights (Sales And Purchases) - Aulia Rahma, Anisa; Suryono, Arief; Saptanti, Noor (CV. Inara, 2024)
This research aims to examine and analyze the legal validity of the Power of Attorney to Sell, which is preceded by a Sale and Purchase Binding Agreement, in the implementation of the Deed of Sale and Purchase if the person giving the power of attorney dies. This research uses normative research methods, is perspective-based, uses a statue approach and a conceptual approach conceptual approach, and the types and sources of data used are primary legal materials, secondary legal materials, and tertiary legal materials. Data collection techniques are carried out through literature studies and interviews, and qualitative data analysis techniques are used. The results of this research show that the legal validity of the Power of Attorney to Sell, which is preceded by a Sale and Purchase Binding Agreement, in the implementation of the Sale and Purchase Deed if the person giving the power of attorney dies is still valid and legal, so that the buyer has legal certainty to carry out the Transfer of Land Rights with reference to the Deed of Sale and Purchase Agreement and Power of Sale. The power of attorney to sell given by the seller to the buyer is a power of attorney that cannot be withdrawn or terminated for any reason. So if all the requirements have been fulfilled, then the process of making a sale and purchase deed can be continued before the PPAT, and transferring the name of the certificate at the land office should proceed as it should even if the person giving the power of attorney (the seller) dies.